Transverse myelitis in myelin oligodendrocyte glycoprotein antibody-associated disease - Perez-Giraldo, Gina; Caldito, Natalia Gonzalez; Grebenciucova, Elena (Frontiers in Neurology, 2023)
Transverse myelitis (TM) is the second most common presentation of myelin oligodendrocyte antibody-associated disease (MOGAD), occurring in approximately 26% of affected patients. The diagnosis may be complicated by the lack of diagnostic specificity of low titers of MOG antibody in serum, fluctuation in seropositivity overtime, including initially normal MRI in up to 10% of patients, and in many instances complete resolution of radiological abnormalities when MRI is done in a significantly delayed fashion. The use of preventive disease modifying treatments is limited by the uncertainty whether the disease process will remain monophasic or become relapsing, as well as by the lack FDA approved treatments. In this review, we discuss clinical, radiological and cerebrospinal fluid (CSF) characteristics, including the significance of MOG titers and changes in the seropositivity status for the diagnosis of MOGAD-associated TM, its radiological features and management options, highlighting the data on the risk of relapses associated with TM at presentation and the need for further randomized clinical trials to empower effective treatment algorithms.